Detection of emergent strains of West Nile virus with a blood screening assay. Issue 6 (8th December 2015) - Faddy, Helen M.; Flower, Robert L.P.; Seed, Clive R.; Ismay, Susan; Ong, Edgar; Linnen, Jeffrey M.; Cory, Robin; Holmberg, Jerry A.; Hall, Roy A.; Setoh, Yin X.; Deerain, Joshua M.; Prow, Natalie A.
Abstract : BACKGROUND: West Nile virus (WNV) is a threat to transfusion safety. WNV Kunjin strain (WNVKUN ) is endemic across parts of Australia; however, human infection is believed to be infrequent and is often associated with relatively minor symptoms. A virulent strain, closely related to WNVKUN (termed WNVNSW2011 ) was recently identified as the etiologic agent of encephalitis in Australian horses. The aim of this project was to investigate whether a commercially available WNV blood screening assay can detect different strains of WNVKUN, including the virulent WNVNSW2011, in human blood donor samples. STUDY DESIGN AND METHODS: Plasma samples were spiked with four different strains of WNVKUN, as well as a prototype WNV strain, at high, medium, and low viral loads. Spiking was confirmed with real‐time reverse transcription–polymerase chain reaction (RT‐PCR), before testing with the Procleix WNV transcription‐mediated amplification (TMA) blood screening assay (Grifols). RESULTS: All WNV strains used were detectable by RT‐PCR after being spiked into plasma. Additionally, all viral spiked samples were reactive by WNV TMA. CONCLUSION: We experimentally demonstrate that a commercially available WNV blood screening assay can detect different strains of WNVKUN . Given that WNV can be transfusion transmissible, it is essential to confirm that emergent strains are detectable by existing blood screening methods.